Two thought games - José Arthur Giannotti; Anthony Doyle (Novos Estudos CEBRAP)
What is the relation between a "truth game" and a "language game"? The former is associated with Heidegger and Foucault, interested either in the essence of truth or its historicity. The latter, with Wittgenstein, who tries to unveil the conditions of the meaning of statements. This article discusses the implications of this opposition, emphasizing the role played by the question of being.